2014
DOI: 10.4161/auto.36293
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy enhances the anticancer activity of silver nanoparticles

Abstract: Abbreviations: ANXA5, annexin A5; CASP3, caspase 3, apoptosis-related cysteine peptidase; CTSB, cathepsin B; DLS, dynamic light scattering; DMEM, Dulbecco's Modified Eagle's medium; EGFP-LC3, enhanced green fluorescent protein-tagged LC3; ICP-MS, inductively coupled plasma-mass spectrometry; I-MEF, immortalized mouse embryonic fibroblast; MDC, monodansylcadaverine; MTOR, mechanistic target of rapamycin; P-MEF, primary mouse embryonic fibroblast; PI, propidium iodide; PI3K, phosphoinositide 3-kinase; PtdIns3K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 50 publications
1
161
0
Order By: Relevance
“…[44][45][46][47] In the current study, we found that AuNPs and AgNPs could act as inducers of autophagy, which are in line with earlier reports. 48,49 The mechanism of AuNPs leading to autophagosome accumulation is due to the blockade of autophagy flux, while that of AgNPs the induction of autophagy. 49,50 Moreover, we further demonstrated that their combination with radiation induced greater levels of autophagy in glioma cells.…”
Section: Promotion Of Autophagy By Aunps or Agnps In Combination Withmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] In the current study, we found that AuNPs and AgNPs could act as inducers of autophagy, which are in line with earlier reports. 48,49 The mechanism of AuNPs leading to autophagosome accumulation is due to the blockade of autophagy flux, while that of AgNPs the induction of autophagy. 49,50 Moreover, we further demonstrated that their combination with radiation induced greater levels of autophagy in glioma cells.…”
Section: Promotion Of Autophagy By Aunps or Agnps In Combination Withmentioning
confidence: 99%
“…48,49 The mechanism of AuNPs leading to autophagosome accumulation is due to the blockade of autophagy flux, while that of AgNPs the induction of autophagy. 49,50 Moreover, we further demonstrated that their combination with radiation induced greater levels of autophagy in glioma cells. Although autophagy is originally defined as type II programmed cell death, researchers have disclosed that autophagy also plays a dual role in cancer development, progression, and treatment.…”
Section: Promotion Of Autophagy By Aunps or Agnps In Combination Withmentioning
confidence: 99%
“…13 In addition, a preferential cytotoxic effect of AgNPs was observed in cells of a breast cancer subtype compared to non-tumorigenic cells derived from the breast, liver, kidney, and monocyte lineages, although the underlying mechanisms were not been determined. 12 Metabolic reprogramming of tumor cells has emerged as a new therapeutic strategy.…”
mentioning
confidence: 99%
“…On the other hand, Lin J and his team also had done some researches for silver nanoparticles [70]. They use HeLa EGFP LC3 to detect autophagy.…”
Section: Nano Agmentioning
confidence: 99%
“…The reaction in 7-10 days increased modestly, and the inflammatory response reaches the top on 30 th day. At the same time, according to the TEM, they found that LC3 II's aggregation and LC3 II protein expression obtained under certain silver nanoparticles concentration, early autophagy is induced, and showed a time dependent, decreased gradually, and ATP may play a significant role on induction of liver toxicity after administered silver nanoparticles.On the other hand, Lin J and his team also had done some researches for silver nanoparticles [70]. They use HeLa EGFP LC3 to detect autophagy.…”
mentioning
confidence: 99%